2010
DOI: 10.1016/j.spinee.2009.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography–evaluated features of spinal degeneration: prevalence, intercorrelation, and association with self-reported low back pain

Abstract: BACKGROUND CONTEXT Although the role of radiographic abnormalities in the etiology of nonspecific low back pain (LBP) is unclear, the frequent identification of these features on radiologic studies continues to influence medical decision making. PURPOSE The primary purposes of the study were to evaluate the prevalence of lumbar spine degeneration features, evaluated on computed tomography (CT), in a community-based sample and to evaluate the association between lumbar spine degeneration features. The seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
1
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(163 citation statements)
references
References 54 publications
4
138
1
12
Order By: Relevance
“…During the CT study, 188 participants were consecutively enrolled in this ancillary study to assess the association between CT-observed characteristics of the lumbosacral spine and back pain. The results of this study were previously reported [14,15].…”
Section: Samplesupporting
confidence: 87%
“…During the CT study, 188 participants were consecutively enrolled in this ancillary study to assess the association between CT-observed characteristics of the lumbosacral spine and back pain. The results of this study were previously reported [14,15].…”
Section: Samplesupporting
confidence: 87%
“…For example, facet joint arthritis was reported to have no relationship with low back pain 5) . According to this report, no form of imaging has proved to be capable of identifying painful facets.…”
Section: Criticism On Diagnostic Labelmentioning
confidence: 99%
“…Choobineh et al (2010) [65] Iran Application of the NMQ in nurses in the operating room. Kalichman et al (2010) [66] Israel Application of the NMQ in persons with spinal degeneration. Kim et al (2010) [67] United States Application of the NMQ in workers in private homes.…”
Section: Hartvigsen Et Al (2005) [55]mentioning
confidence: 99%
“…The results showed that 71.2% of them presented pain in the knees and in the lower back, all associated with depression and a poor quality of life. Kalichman et al [66], with the help of the NMQ, among other observations, studied the degeneration of the spinal column in the lumbar area. Only the spinal stenosis showed a statistically significant association with lumbalgia.…”
Section: Pathologies Health and Ageingmentioning
confidence: 99%